Relationship between Knowledge Hypertension Complications and Medication Adherence among Elderly with Comorbidities - Anisa Anggraeni; Arina Maliya (Indonesian Journal of Global Health Research, 2026)
Hypertension continues as a distinct global health issue and is associated with the risk of developing multiple complications, as well as premature death. The high prevalence of hypertension at the global and national level, as well as low awareness and poor control in elderly patients with comorbidities typifies a major challenge to hypertension control. Knowledge on the complications of hypertension is assumed to significantly contribute to medication adherence behavior. This research was conducted with the purpose of investigating the correlation between knowledge level on complications caused by hypertension and medication adherence behavior in hypertensive patients who have comorbidities at Kartasura Health Center. Study Design This is a quantitative study with correlational design method and cross-sectional approach. The sample of this study was 70 respondents taken with total sampling technique. Data collection was done with a questionnaire measuring knowledge of hypertension complications using the Guttman scale (15-items) and Morisky Medication Adherence Scale-8 (MMAS-8) to measure the medication adherence. The results of the validity and reliability tests indicated that the hypertension complication knowledge questionnaire demonstrated a validity coefficient of r = 0.349 and a reliability coefficient of 0.70812, indicating that the instrument was valid and reliable. Meanwhile, the Morisky Medication Adherence Scale-8 (MMAS-8) showed a validity value of p = 0.5 and a reliability coefficient of 0.83, confirming that the instrument was valid and highly reliable for measuring medication adherence. Analyses were completed with univariate and bivariate analysis, and the use of a Spearman rank correlation test (significance level was set at α = 0.05).Among the respondents, majority of them had a good level of knowledge on complications associated with hypertension (47.14%) and over half of them also had a low medication adherence rate (54.29%). A strong and statistically significant positive relationship between the knowledge level of hypertension complications and drug adherence were found according to the Spearman's rank correlation test (ρ = 0.680, p = 0.001). The more knowledge the subjects had, the more tended to be adherence to antihypertensive medications. The level of knowledge about complications in hypertension showed a strong association with drug adherence among elderly patients with comorbidities.